"The future of the internet hangs in the balance": the perception and framing of political opportunity and threat in the contentious politics of data. - Wright, Jared M. (Social Movement Studies, 2024)
Opportunities are often conceptualized as 'openings' in a social movement's external environment which can reduce the cost of collective action, while threat is a force which increases the cost of inaction. These concepts were originally formulated to describe the political contexts of traditional offline movements, therefore how are they perceived and framed by activists in the digital environment of data? This study utilizes qualitative thematic coding to examine the collective action frames in four years of archival texts from 2009 to 2012 of two highly adept data activist mobilizations: The Digital Rights movement and the Anonymous hacktivist collective. Analyses show that frames of opportunity appear with far less frequency than threat. For both cases, volatile opportunity frames regarding their online actions are very rare, especially in the Anonymous texts. It concludes by suggesting that highly leveraging the affordances of digital technology and data may lead to political opportunities losing some of their perceived salience as a mobilizing force, while cultural factors around data activism may simultaneously result in an increased perception of threats. This study shows the importance of understanding how data mediate contemporary collective action and calls for further development and synthesis of the structural and cultural aspects of both opportunity and threat in social movement theory.